NEOSQUIRREL: a data set of ecological knowledge on Neotropical squirrels. (25th April 2019) - Mendes, Calebe Pereira; Koprowski, John L.; Galetti, Mauro
Abstract: The squirrels (Sciuridae), with 292 species, make up the second most diverse family of rodents. Squirrels play important roles as seed and spore dispersers and seed predators in all regions where they occur. In Neotropical regions, around 28 species of squirrel are recognised. However, our knowledge of the ecology of the Neotropical Sciuridae is severely incomplete, lacking in the most basic ecological information for most species. We reviewed the literature in English, Spanish, and Portuguese, for all squirrel species in the Neotropical biogeographic region, summarising ecological interactions between squirrels and the local biota, population density records, the number of publications, and the distribution of study sites. We found information for 20 squirrel species (71% of the recognised species), from 15 countries, in 48 publications containing 126 population density records and 155 publications containing 649 ecological interactions. The most studied species were Guerlinguetus brasiliensis, Notosciurus granatensis, and Sciurus variegatoides, with 53% of all publications, whereas for eight species of Microsciurus, we found no publications. The density of Neotropical squirrels varied from 0.08 to 100 individuals per km 2 and was negatively correlated with forest area. Neotropical squirrels were recorded eating 174 plant taxa, five fungus taxa, four invertebrate taxa, and one species of vertebrate. Palms were common in the diet of squirrels (30 palm species, 27% of feeding records). Squirrels cached 28 plant species, of which 15 were palms. Sixty‐five taxa of parasites are documented to occur in Neotropical squirrels, and the most common were Enderleinellus lice. Zoonotic parasites, including trypanosomes, Leptospira spp., Leishmania spp., and plague were also reported. Our review reveals the main information gaps in the current knowledge about the ecology of Neotropical Sciuridae and maps the geographic distribution of the available information throughout South and Central America. Squirrels often thrive in small forest fragments and fulfil important roles as seed dispersers and prey for mesopredators.